Comparative Phylogeography of Veronica spicata and V. longifolia (Plantaginaceae) Across Europe: Integrating Hybridization and Polyploidy in Phylogeography - Buono, Daniele; Khan, Gulzar; von Hagen, Klaus Bernhard; Kosachev, Petr A.; Mayland-Quellhorst, Eike; Mosyakin, Sergei L.; Albach, Dirk C. (Frontiers in Plant Science, 2021)
Climatic fluctuations in the Pleistocene caused glacial expansion-retraction cycles in Eurasia and other areas of the world. Consequences of these cycles, such as population expansion and subsequent subdivision, have been studied in many taxa at intraspecific population level across much of the Northern Hemisphere. However, the consequences for the potential of hybridization and polyploidization have mostly been overlooked. Here, we investigated the phylogeographic structure of two widespread, closely related species, Veronica spicata and V. longifolia, across their European distribution ranges. We have assessed the extent of natural hybridization and the geographic pattern of polyploidization in both species. We used genome-scale SNP data to clarify phylogenetic relationships and detect possible hybridization/introgression events. In addition, crossing experiments were performed in different combination between V. spicata and V. longifolia individuals of two ploidy levels and of different geographic origins. Finally, we have employed ecological niche modelling to infer macroclimatic differences between both species and both ploidy levels. We found a clear genetic structure reflecting the geographical distribution patterns in both species, with V. spicata showing higher genetic differentiation than V. longifolia. We retrieved significant signals of hybridization and introgression in natural populations, both through the genetic data and crossing experiments. However, there were no clear geographic patterns of polyploidization. The crossing experiments produced viable hybrids when the crosses were made between plants of the same ploidy levels but not in interploidy crosses. The results suggest that hybridization occurs across the overlapping areas of natural distribution ranges of both species, with apparently directional introgression from V. spicata to V. longifolia. Nevertheless, the two species maintain their species-level separation due to their adaptation to different habitats and spatial isolation rather than reproductive isolation.